Recherche im Translationsprozess Ein Lehr- und Studienbuch - Hagemann, Susanne (Frank & Timme, 2022)
What do I need to know in order to successfully complete a translation job? How do I acquire the relevant knowledge? This is what information mining is about. Gaps in a translator's knowledge can occur in a variety of areas, including linguistic or cultural competence, technological competence, background knowledge about the subject area in question, the details of the translation brief, and familiarity with the requirements of professional practice. This textbook will guide students through the various stages of the information-mining process. The book begins by showing how to identify individual knowledge deficiencies. It then proceeds to discuss ways of finding appropriate resources and evaluating possible solutions, and concludes by providing an overview of options for documenting results for later use. Numerous examples and illustrations facilitate comprehension.